Pelatihan Teknik Membaca Puisi Mahasiswa Universitas Islam Riau - Wilda Srihastuty Handayani Piliang; Fatmawati Fatmawati; Rika Ningsih; Rhani Febria (UIR Press, 2023)
This training aims to overcome the difficulties of Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Riau Islamic University (UIR) students in reading poetry with good and correct techniques. Students often experience difficulties in identifying the elements of poetry, using the right intonation, and emphasizing the appropriate tone and rhythm. Poetry reading technique training is expected to increase their understanding of poetry and their ability to convey poetry effectively. In addition, the integration of poetry reading techniques in education has significant benefits in the development of language skills, literary comprehension, public speaking skills, cultural awareness, creativity and imagination of students. The implementation of this training involved participants who were 119 students of Pendidikan Bahasa dan Sastra Indonesia (PBSI) UIR. The training includes demonstrations of reading poetry and debriefing poetry reading techniques by experienced practitioners of literature. Understanding the script, breathing exercises, expressions, gestures, intonation, and volume are explained as important aspects in reading poetry effectively. The results and discussion of this training are expected to contribute to the development of literary education in the UIR academic environment.